2015
DOI: 10.1016/j.im.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of formal controls in facilitating information system diffusion

Abstract: Information systems (IS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
6
0
3
Order By: Relevance
“…However, we found that attitude may be influenced by facilitating conditions and social influence, which are the contextual factors in our model. This is perhaps not completely surprising-facilitating conditions such as training programs and help desks may be instrumental in enabling individuals to form positive attitudes about the technology (e.g., Chiu et al 2012;Pynoo et al 2007;Ravishankar 2008;Sahu and Gupta 2007;Sandeep and Ravishankar 2014) whereas individuals may also refine their attitudes based on information or stories shared by others who have already adopted the technology (e.g., Abubakre et al 2015;Chiu et al 2012;Pynoo et al 2007;Sumak et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that attitude may be influenced by facilitating conditions and social influence, which are the contextual factors in our model. This is perhaps not completely surprising-facilitating conditions such as training programs and help desks may be instrumental in enabling individuals to form positive attitudes about the technology (e.g., Chiu et al 2012;Pynoo et al 2007;Ravishankar 2008;Sahu and Gupta 2007;Sandeep and Ravishankar 2014) whereas individuals may also refine their attitudes based on information or stories shared by others who have already adopted the technology (e.g., Abubakre et al 2015;Chiu et al 2012;Pynoo et al 2007;Sumak et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Behavior control, being a blend of rules, guidelines, standard operating procedures and practices, provides a basis for enhanced construction project performance (Abubakre et al, 2015). Regular meetings, walkthroughs and weekly or monthly reports are some of the typical mechanisms to achieve behavior control (Ning, 2017).…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Studies attest that managing change within an organization is problematic, requiring the adoption of a methodological approach involving stakeholders across the organization to realize consistent successful outcomes (Buchanan et al, 2005;Burnes, 2005;Pettigrew and Whipp, 1993). Organizations have struggled with the cultural aspects of change especially in large government and health related sectors where projects have suffered from user resistance, poor change agent performance and related political factors (Abubakre et al, 2015;Cinite et al, 2009;McDermott et al, 2013;Sandeep and Ravishankar, 2014;Warne and Hart, 1997).…”
Section: Poor Change Managementmentioning
confidence: 99%